2022
DOI: 10.1155/2022/8978152
|View full text |Cite|
|
Sign up to set email alerts
|

Virtual Reality Technology of New Media Visual Simulation

Abstract: In order to improve the exhibition effect of museums and expand the display ways of digital museums, a Chinese museum scene roaming application system based on the Unity 3D virtual reality engine was proposed. 3Dmax model production software was used to complete the museum scenes and the model production, material, and lighting of collections in the museum. Through the Unity 3D virtual reality engine, the design and production of the interactive system were completed. The display and application of the scene r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The construction of the Digital Twin model is oriented to meet the actual business needs and solve specific problems, with "eight uses" (usable, universal, quick use, easy to use, joint use, joint use, live use, and good use) as the goal, "four trends" of the digital twin model (precision, standardization, lightweight, and visualization) [10][11][12][13] as the requirements, and "four cans" (interactable, convertible, reconfigurable, and evolvable) in its operation and operation as the requirements, and explored and established the theoretical system of "construction-assembly-fusion-verificationvalidation-management" for the modelling of the digital twin model [14][15][16] .The schematic diagram of the equipment digital twin is shown in Figure 3.…”
Section: Digital Twinmentioning
confidence: 99%
“…The construction of the Digital Twin model is oriented to meet the actual business needs and solve specific problems, with "eight uses" (usable, universal, quick use, easy to use, joint use, joint use, live use, and good use) as the goal, "four trends" of the digital twin model (precision, standardization, lightweight, and visualization) [10][11][12][13] as the requirements, and "four cans" (interactable, convertible, reconfigurable, and evolvable) in its operation and operation as the requirements, and explored and established the theoretical system of "construction-assembly-fusion-verificationvalidation-management" for the modelling of the digital twin model [14][15][16] .The schematic diagram of the equipment digital twin is shown in Figure 3.…”
Section: Digital Twinmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%